The Effect Of Self-Reliance And Self-Efficacy On Student's Financial Education - Vella Anggresta; Hayu Stevani; Rendika Vhalery; Maria Oktasari (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2019)
Educating oneself about financial education as recent investment is a necessity, so that there is a need to conduct a study to avoid the financial problems appeared. This study aims to investigate the students' financial education level based on self-reliance and self-efficacy aspects. There were 317 students of Indrapasta PGRI university involved in this study. The data were analyzed by using multiple regression preceded by classic assumption test. The result showed that those three hypotheses are accepted. The effect of self-reliance and self-efficacy is 30.1% and other factors which are not discussed in this study affect as 69.9 %.Keyword: self-reliance, self-efficacy, financial education